Larangan Perkawinan Sesuku dalam Masyarakat Minangkabau Ditinjau dari Hukum Adat dan Hukum Islam - Desstuliadi Destuliadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this research is to find out how customary law and Islamic law view the prohibition of same-ethnic marriage in Minangkabau society. This research uses a socio-legal approach and is supported by a descriptive analysis approach. This legal approach is qualitative. The results of the study show that there is no conflict between Islamic law and customary law. If same-ethnic marriage occurs, Islamic law does not prohibit it, but Islamic law allows it. Islamic law prohibits marriage, this includes the ban on marrying forever and the ban on marrying for a certain time or temporarily. Violators of tribal marriages usually receive sanctions such as fines and exile. The conclusion of this study found that same-ethnic marriage in Minangkabau society in the village is abstinence marriage because it can damage the Minangkabau customary law system. Same-sex marriage violators will be fined and banished. Keywords: Marriage, Customs and Tribes